Gestión administrativa de las instituciones de educación superior: Universidad Católica de Cuenca-Ecuador : Administrative management of higher education institutions: Catholic University of Cuenca-Ecuador - Ordóñez Parra, Janice; Cárdenas Muñoz, Jorge; Cuadrado Sánchez, Gina; Zamora Zamora, Geovanny (Revista de Ciencias Sociales, 2021)
Higher education institutions regardless of their geographical-social context must maintain continuous improvement processes in the various value-generating activities related to teaching, links with the community and research, as well as enabling activities, which is why it is necessary to have with a solid and effective internal control system in order to obtain efficiency, effectiveness and population satisfaction. Therefore, the objective is to analyze the administrative management of higher education institutions, in the case of the Academic Unit of Administration at the Catholic University of Cuenca-Ecuador through the evaluation of internal control applying the model proposed by the Committee of Sponsoring Organizations of the Treadway Commission, to contribute to its improvement. The methodology is descriptive framed in a qualitative, cross-sectional and deductive approach, supported by the literature review. The results reveal a confidence level of 68% and a risk level of 32%. Concluding that the weaknesses established in administrative management respond to the lack of risk plans, contingency procedures,